NIGERIAN LANGUAGES: (IGBO, HAUSA, YORUBA...): TOOLS FOR BETTER ENTREPRENEURSHIP IN NIGERIA - L. DOM-ANYANWU, DR. NGOZI (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
The indigenous language of a child is so natural that the child thinks in it in every aspect. The knowledge acquired by the child can never be erased as long as indigenous language/mother-tongue is involved. The aim of this paper is to establish the role of indigenous languages in the effective learning of entrepreneurship in Nigeria schools/education. It looks at the types of entrepreneurship, its economic benefits and the benefits of using indigenous languages as medium of instruction in achieving the goal of an entrepreneur. The paper concludes that skills and businesses are effectively learned using the indigenous languages as medium of instruction than using the foreign languages as medium of instruction, which the learner may find difficult to understand. This will go a long way in positively affecting the growth of business education as a filed.